Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Media Smart Kuartet terhadap Kemampuan Pemahaman Konsep Siswa - Tri Sundari Lia Oktaviani; Zulmi Roestika Rini (Journal on Education, 2025)
The study addresses the issue of students' low conceptual understanding. It aims to examine the influence of the Teams Games Tournament (TGT) model supported by Smart Quartet media on enhancing students' conceptual comprehension. This quantitative research employs a quasi-experimental method with a nonequivalent control group design. Purposive sampling was used to select the participants, comprising grade 4 students from SDN Gondoriyo 02 and SDN Gondoriyo 03. Data collection techniques included both tests (pretest and posttest) and non-tests (observations, questionnaires, unstructured interviews, and documentation). The data analysis involved normality tests, homogeneity tests, independent sample t-tests, and simple regression tests. The findings revealed two key results: (1) A significant difference was observed in students' conceptual understanding when the TGT model with Smart Quartet media was applied. This was supported by an independent sample t-test significance value of 0.030 < 0.05. (2) The TGT model with Smart Quartet media positively influenced students' conceptual understanding, as indicated by a linear regression test significance value of 0.027 < 0.05. In conclusion, the Teams Games Tournament model assisted by Smart Quartet media significantly enhances the conceptual understanding of grade 4 students, highlighting its effectiveness in improving educational outcomes.